2018
DOI: 10.3390/molecules23082023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhizome Extract of Dioscorea batatas and Its Active Compound, Allantoin, on the Regulation of Myoblast Differentiation and Mitochondrial Biogenesis in C2C12 Myotubes

Abstract: With the aging process, a loss of skeletal muscle mass and dysfunction related to metabolic syndrome is observed in older people. Yams are commonly use in functional foods and medications with various effects. The present study was conducted to investigate the effects of rhizome extract of Dioscorea batatas (Dioscoreae Rhizoma, Chinese yam) and its bioactive compound, allantoin, on myoblast differentiation and mitochondrial biogenesis in skeletal muscle cells. Yams were extracted in water and allantoin was ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The obesity-related loss of skeletal muscle, referred to as sarcopenia, is associated with the dysregulation of glucose metabolism and accelerated loss of muscle loss [69]. Therefore, a number of studies have focused on the mechanisms of this skeletal muscle dysfunction, as well as interrogating potential nutritional interventions, including the use of diets rich in protein, which could help retain muscle strength [70,71]. The present study has shown that SP increases the expression of genes involved in skeletal muscle differentiation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The obesity-related loss of skeletal muscle, referred to as sarcopenia, is associated with the dysregulation of glucose metabolism and accelerated loss of muscle loss [69]. Therefore, a number of studies have focused on the mechanisms of this skeletal muscle dysfunction, as well as interrogating potential nutritional interventions, including the use of diets rich in protein, which could help retain muscle strength [70,71]. The present study has shown that SP increases the expression of genes involved in skeletal muscle differentiation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma SH-SY5Y cells (5 × 10 4 cells/well) were seeded into each well. After 24 h incubation of the cells at 37 • C under 5% CO 2 , the sample was added to each well in four different concentrations (10,25,50, 100 µM), and the mixture was preincubated for 1 h. Then, the toxicity inducer 6-OHDA (6-hydroxy dopamine hydrobromide) was added, and the mixture was further incubated for 2 h. Ten microliters of resazurin was added to each well 1 h before the end of the incubation to obtain the final resazurin concentration of 0.01 mg/mL. Finally, the neuroprotective activity of each sample against 6-OHDA was determined by measuring the fluorescence intensity at 530 nm excitation and 590 nm emission wavelengths using a microplate reader.…”
Section: Assay For Neuroprotective Activitymentioning
confidence: 99%
“…With an increasing age, the sarcopenia becomes regarded as a significant concern, which poses a substantial social and economic burden. In spite of great trials to pursue and develop agents and therapies, they remain unsatisfactory due to little convincing evidence and efficacy or accompanying side effects [6,7]. Currently, exercise training has been considered as a primary treatment for the sarcopenia or the muscle atrophy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of great trials to pursue and develop agents and therapies, they remain unsatisfactory due to little convincing evidence and efficacy or accompanying side effects [6,7]. Currently, exercise training has been considered as a primary treatment for the sarcopenia or the muscle atrophy [6,7]. However, there is a limitation to suggest exercise training as an intervention for sarcopenia because elderly people and sarcopenia patients are likely to be bed-ridden due to illness or frailty [1,2].…”
Section: Introductionmentioning
confidence: 99%